La cooperación política en el ámbito migratorio: la lucha contra las mafias y el crimen organizado - Anguita Olmedo, Concepción (Revista Española de Desarrollo y Cooperación, 2023)
It will not be until the decade of 1990 when the organized crime takes shape as a phenomenon that affects the globalized international society. Prevention and repression, as the main instruments that are currently put into practice, show a deficit in the fight against the organized crime. These insufficiencies demand a better execution of development and cooperation policies with a multilateral dimension, facing from his base the causes that propitiate it.